Dynamics Simulation Analysis and Experimental Research of Gear Broken Tooth Failure Mechanism of Diesel - Jiang Zhinong; Jiang Bing; Zhang Chuangang; Xing Chenghong; Zhang Jinjie (Jixie chuandong)
The model of diesel gear transmission system（ crank,crank gear,the intermediate gear,camshaft gear and camshaft） in an inline six-cylinder diesel engine is established to study. The multi-body dynamics simulation software ADAMS is used to simulate the frequency change of camshaft gear in normal and the fault of broken teeth,camshaft axial moving and intermediate gear radial vibration. Then the results are compared with the experimental data of gear broken tooth of diesel engine and comparison result shows that,when camshaft gear break tooth,each order frequency will increase,especially the fundamental frequency,three frequency multiplication,and four frequency multiplication. The phenomenon is identical with the actual failure case. When camshaft axial moving and intermediate gear radial vibration,each order frequency will increase significantly,especially the fundamental frequency,three frequency multiplication,and four frequency multiplication. Therefore,both cases may have resulted gear does not run smoothly,resulting in broken teeth failure.